2021
DOI: 10.15252/embj.2020107237
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic reconfiguration of pro‐apoptotic BAK on membranes

Abstract: BAK and BAX, the effectors of intrinsic apoptosis, each undergo major reconfiguration to an activated conformer that self‐associates to damage mitochondria and cause cell death. However, the dynamic structural mechanisms of this reconfiguration in the presence of a membrane have yet to be fully elucidated. To explore the metamorphosis of membrane‐bound BAK, we employed hydrogen‐deuterium exchange mass spectrometry (HDX‐MS). The HDX‐MS profile of BAK on liposomes comprising mitochondrial lipids was consistent w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 58 publications
(146 reference statements)
2
19
0
Order By: Relevance
“…7 inset and Supplementary Movie 1 ). NMR and hydrogen-deuterium exchange mass spectrometry experiments showed that residues 1–65 are intrinsically disordered in BH3 ligand-activated BAK 31 , 32 . Corroborating this mechanism, the T m of activated BH3-BAK complexes is lower than that of apo BAK, and autoactivation proceeds at lower doses of protein with mutants that disrupt the electrostatic network stabilizing helix α1 in apo BAK.…”
Section: Discussionmentioning
confidence: 99%
“…7 inset and Supplementary Movie 1 ). NMR and hydrogen-deuterium exchange mass spectrometry experiments showed that residues 1–65 are intrinsically disordered in BH3 ligand-activated BAK 31 , 32 . Corroborating this mechanism, the T m of activated BH3-BAK complexes is lower than that of apo BAK, and autoactivation proceeds at lower doses of protein with mutants that disrupt the electrostatic network stabilizing helix α1 in apo BAK.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by HDX-MS showed that the activation of liposomes-bound BakΔC by cBid was associated with an increase in the disorder of the N-terminal part of the protein, leading to a decrease in potential interactions between helix α1 and helices α6–α8 [ 78 ]. This suggests that the N-terminal part of Bak has somehow a negative regulatory function on the activation process.…”
Section: Do Bcl-2 Family Proteins Actually Need Mitochondrial Receptors?mentioning
confidence: 99%
“…In an irreversible step toward cell death, BAK and BAX promote apoptosis via mitochondrial outer membrane permeabilization (MOMP) in response to a variety of signals (Tait & Green, 2010). Structural, biochemical, and cell biological studies have illuminated some aspects of the mechanism of membrane permeabilization by BAK and BAX, yet a full understanding remains elusive due to the dynamic nature of these proteins, the lipid environment in which they function, and the complex multilayered BCL-2 network that provides regulatory control (Sandow et al, 2021) (Delbridge et al, 2016). In this study, we addressed early steps in the activation of BAK in which the binding of certain BCL-2 family members to form heterodimers leads to a conformation change that is required for downstream steps including BAK dimerization and higher-order oligomerization.…”
Section: Introductionmentioning
confidence: 99%